Implementasi Metode Pembelajaran Blended Learning Untuk Mengembangkan Kemampuan Kognitif Anak Usia Dini di POS PAUD Mawar Kabupaten Purworejo - Pramudya Elentika (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to obtain information on the implementation of the blended learning method at PAUD Mawar, Kemiri District, Purworejo Regency. PAUD Mawar, Kemiri District, Purworejo Regency, Central Java Province. Established since 2008 and developing a blended learning method. The implementation of this method is generally carried out with various activities that are individual or group in nature. The activities carried out are direct practice activities that emphasize cognitive abilities in children and the role of parents